Anticancer Inhibitors - Fantacuzzi, Marialuigia; Ammazzalorso, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The word "cancer" is associated with at least 100 different pathologies, depending on the organ involved and the type of tumor developed. Cancer is a complex disease involving multiple pathogenetic mechanisms. Characterization of different types of cancers, which distinguishes them from healthy cells and other cancers, allows for the identification of specific targets for each individual tumor. The principle of chemotherapy is based on interference with the mechanisms that regulate the life and proliferation of cancer cells, causing their death. In recent years, there has been continuous progress in the development of therapeutic agents against cancer, which is ongoing.The Anticancer Inhibitors Special Issue focuses on new target-based anticancer agents that inhibit a specific target involved in the suppression of various types of cancer and the control of their chemoresistance.There is a collection of research and review articles on advances in drug discovery, design, and development of new inhibitor compounds with potency against various cancer types.